EFEKTIVITAS CERITA BERGAMBAR DIGITAL BERBASIS CANVA TERHADAP KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR KELAS RENDAH - Syntia Hanna Adila; Prana Dwija Iswara; Diah Gusrayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading skills are an important basic skill to be mastered by elementary school students, especially at the low grade level. However, in practice, many students have difficulty understanding the content of reading due to the use of less attractive learning media. This study aims to determine the effectiveness of digital picture story media based on Canva application on reading skills of grade II students of SD Negeri Sukaraja 1. This study used a quantitative approach with a quasi-experimental design in the form of Nonequivalent Control Group Design. The research sample consisted of two grade II classes selected through purposive sampling technique, namely the experimental class of 27 students and the control class of 28 students. The experimental class was treated using Canva-based digital picture story media, while the control class used conventional media. The research instruments included reading skill tests and student interviews. The Mann-Whitney test results on pretest scores showed no significant difference between the experimental and control classes (p = 0.249 > 0.05), which means that the students' initial abilities were comparable. After the treatment, the Wilcoxon test showed a significant improvement in the experimental class, and the Mann-Whitney test on the posttest showed a significant difference between the two classes. The interview results also showed that students gave positive responses to the use of the media. Thus, the Canv-based digital picture story media.